PENGARUH KEPEMIMPINAN KEPALA DESA TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA TANJUNG BATU KECAMATAN TENGGARONG SEBERANG - Musriadi Musriadi (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2012)
The purpose of this study was to determine whether the leadership of an impact on people's participation in development. To obtain the necessary data, the authors conducted research in sub Desa Tanjung Batu Seberang Tenggarong Kutai regency.Thus the Leadership Village Chief affect people's participation in rural development in sub Desa Tanjung Batu Seberang Tenggarong Kutai regency acceptable because it has been proven the true.Key words: leadership, participation, development, Tanjung Batu.